Application of water-saving irrigation technologies in the irrigation of fodder beets grown as the main crop - Khodirov Z; Jumaev J; Oripov I (Zien Journals, 2023)
Soil reclamation conditions are the main factor in the growth and high yield of fodder beetroot and its crops. Therefore, in the care of agricultural crops, it is important to selectively plant and place crops according to soil reclamation and fertility. A number of research scientists in this regard, including A.S. Bolkunov [100 pp. 149–154], K.K. Gedroys [101; p. 247], I.V. Tyurin [102; p. 320], W.R. Williams [103; p. 311], V.V. Dokuchaev [104; p. 45], N.K. Baliabo [105; p. 446], A.K. Kashkarov [106; pp. 175–182], V.P. Kondratyuk [107; pp. 122-130], V.A. Kovda [108; p. 324], P.P. Vavilov [109; pp. 438–457], R. Oripov [110; p. 95–40], Hamraev K [111; p. 39–40], and other scientists have carried out a lot of scientific work on the effects of irrigation and feeding regimes and methods of maintaining soil fertility and improving its reclamation condition. Our experimental field is located in the sandy zone of the Bukhara region, so it belongs to the lower regions with sandy and loamy soil. The hydrogeological conditions of the areas controlled by the Shahrud Dostlik Main Canal are changing; therefore, the level of seepage water is changing in these areas.
Keywords: Shahrud; changing; reclamation; experimental